The Stepping into Visibility Model: reflecting on consequences of social media visibility – a Global South perspective. Issue 2 (25th January 2023) - Rega, Isabella; Medrado, Andrea
ABSTRACT: This article discusses activists' need to reflect on how achieving social media visibility might translate into vulnerability. In order to provide activists with a tool for this reflection, the Stepping into Visibility Model has been developed and applied to two case studies: (a) an activist group in a Brazilian favela using social media for protection against police brutality and (b) a Kenyan photographer, affiliated to an art-ivist (artistic and activist) collective, producing images of Nairobi at night to tackle social anxiety issues. The research draws from sociological insights on the concept of 'visibility' and adopts a case study methodology combined with ethnographic approaches. By adopting a Global South perspective, it discusses counter surveillance efforts in ways that go beyond techno-legal solutionism (Dencik et al, 2016 ) and in periods outside that of big-scale protests (McCosker, 2015 ). By devising this model, we hope to offer a contribution on how marginalised communities can be better informed when they encounter unintended negative visibility.